Vickers micro-hardness study of the effect of fluoride mouthwash on two types of CAD/CAM ceramic materials erosion - Hamid Kermanshah; Elham Ahmadi; Niyousha Rafeie; Shiva Rafizadeh; Ladan Ranjbar Omrani (BMC, 2022)
Abstract Background The aim of this study was to evaluate the protective effects of fluoride mouthwash on the surface micro-hardness of two types of CAD/CAM ceramics after exposure to acidic solutions. Methods 40 samples (5 × 5 × 3 mm3) were prepared from two different ceramics: Vitabloc Mark II CAD, and IPS e.max CAD. The samples were randomly divided into 5 groups in each ceramic (n = 8) immersed in different solutions: Gs: saliva: GGA: gastric acid, GAA: acetic acid, GFGA: sodium fluoride + gastric acid, GFAA: sodium fluoride + acetic acid. The microhardness of samples was measured before and after immersion in different solutions by Vickers microhardness tester. By subtracting the microhardness values after and before immersion, the microhardness changes of the samples were obtained. Data were analyzed by Two-way analysis of variance, one-way analysis of variance, and Tukey test (α = 0.05). Results Immersion in different solutions reduced the microhardness. Microhardness loss was significantly affected in G FAA and G FGA groups in both types of ceramics (P < 0.05). For Vitabloc Mark II groups, the microhardness loss was significantly higher in GFAA and GFGA compared to IPS e.max CAD P < 0.001). Conclusion Fluoride mouthwash in conjunction with acidic solutions may adversely affect microhardness of Vitabloc Mark II CAD, and IPS e.max CAD that may consequently compromise the clinical service. Vitabloc Mark II CAD was significantly more affected than IPS e.max CAD.